EXPERIENCE IN USING HIGHLY HYDROLYZED MILK FORMULAS IN NUTRITION OF INFANTS WITH ATOPIC DERMATITIS - R.M. Faizulina; E.T. Khusainova; A.A. Ismagilova; M.A. Rakhmatullina ("Paediatrician" Publishers LLC, 2008)
The article reviews an urgent problem of pediatrics, alimentary therapy of children with atopic dermatitis (ATD). The article summarizes the author's experience of using milk formulas based on highly hydrolyzed cow's milk casein (nutramigen and pregestimil) for alimentary therapy of infants with medium grave and grave ATD and gastrointestinal presentation of food allergy during the acute period. The best tolerance of the above mentioned formulas is recommended for infants under 6 months. Besides, it is observed that feeding results in reduced scored index, normalized characteristics of physical development, enhanced indices of functional status of alimentary system. The analysis of observation results permits to recommend milk formulas based on highly hydrolyzed cow's milk casein for alimentary therapy of infants under 12 months, suffering from ATD.Key words: infants under 12 months, atopic dermatitis, alimentary therapy.